'Catch Them Being Good': preliminary findings from a brief parenting intervention. Issue 10 (27th July 2021) - Westwood, Sue; Faelling, Joanne; Sutton, Carole
ABSTRACT: Although the use of praise for young children is well documented, its use in a stand-alone intervention warrants further exploration. This study aimed to determine whether a brief intervention to raise parental awareness of effective praise had any significant impact on children's behaviour. A mixed methods, control group design was used to evaluate the 'Catch Them Being Good' Initiative with parents of children aged between 2 and 4. Results from pre and post measures from the Strengths and Difficulties Questionnaire and post intervention interviews showed promising results. Those who took part in the intervention reported a reduction in their child's behavioural problems and an increase in prosocial behaviour. Focusing on positive behaviours helped parents to break the cycle of attending to bad behaviour. This light-touch approach empowered parents to make small changes to their parenting practice that resulted in significant improvements in their children's' behaviour.